The contribution of the low-fee private school sector towards access to quality education: a case study of two low-fee private school models - Ramulongo, Nduvho Theony (My University, 2016)
The research investigates the contribution of the low-fee private school sector towards access to quality education by examining two models of low-fee private schools in the Gauteng province, South Africa. The study generates insights about the contribution to quality education and implications of a growing low-fee private school sector for equity in the South African context. It looks at the factors that encourage the growth of the sector, the nature and challenges of running private schools and the quality of education offered by low-fee private schools. The study uses an exploratory qualitative research methodology and a case study design. Elite interviews with three experts; three founding directors; principals and two teachers from two low-fee private schools (one non-profit and the other one for-profit) in Bramley, Johannesburg were used as data collection instruments. The findings reveal that government support for private schools post-1994; excess demand due to middle class population growth in certain areas and differentiated demand owed to better quality and faith-based education are the key factors driving the growth of the private school sector in South Africa. The quality of education offered by low-fee private schools in South Africa is different across schools and mirrors the inequalities in the public school system. With reference to the literature, it is clear that the low-fee private school sector plays a noteworthy role, ensuring that some learners have access to schools in areas where government has not been able to keep up with the middle class population growth. Low-fee private schools give parents the opportunity to choose faith-based schools in a country where the public education system is faith-neutral. Although low-fee private schools are viewed as an alternative from public schools due to the poor quality offered by the latter, it is important to note that there are great differences with the quality offered by different schools in the private sector.
Submitted in partial fulfilment of the requirements for the degree of Master of Education in the Faculty of Humanities at the University of the Witwatersrand, September 2016
Keywords: Education--South Africa--Costs; Private schools--South Africa--Costs